The Plot of Luke's Story of Jesus - Kingsbury, Jack Dean 1934- (1994)
In the story of Luke's Gospel, the primary conflict at the human level is that between Jesus and the religious authorities. This conflict, while it reaches its culmination in the death, resurrection, and ascension of Jesus, comes to its head in the episode of Jesus on the cross. Whereas the authorities believe that Jesus' death vindicates them as Israel's rightful rulers, the reader knows that, ironically, the cross is the place where Jesus is at once publicly proclaimed as Israel's Messiah-King and anticipates the onset of his glorious reign of salvation.